1998
DOI: 10.1163/156856298x00316
|View full text |Cite
|
Sign up to set email alerts
|

Elastic protein-based polymers in soft tissue augmentation and generation

Abstract: Five elastic protein-based polymers, designed as variations of polymer I, (GVGVP)251, elicited different responses when injected as subcutaneous implants in the guinea pig, a preclinical test used to evaluate materials for soft tissue augmentation and specifically for correction of urinary incontinence. All six polymers, prepared using recombinant DNA technology, expressed at good levels using transformed E. coli fermentation. These E. coli-produced polymers were purified for the first time to the exacting lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(67 citation statements)
references
References 39 publications
2
64
0
1
Order By: Relevance
“…Biological materials such as elastin-based polypeptides, collagens derived from extracellular matrices, fibrins, and spider silk proteins [59,62,153,[183][184][185][186][187] are useful for tissue engineering because they have good chemical compatibility in aqueous solutions, good in vivo biocompatibility, a controllable degradation rate in vivo, the ability to break down into natural amino acids that can be metabolized by the body, and minimal cytotoxicity, immune response, and inflammation [174,[188][189][190][191][192][193][194]. In addition, biopolymers can be easily functionalized to enhance their interactions with cells and provide an optimal platform for cellular activities and tissue functions.…”
Section: Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological materials such as elastin-based polypeptides, collagens derived from extracellular matrices, fibrins, and spider silk proteins [59,62,153,[183][184][185][186][187] are useful for tissue engineering because they have good chemical compatibility in aqueous solutions, good in vivo biocompatibility, a controllable degradation rate in vivo, the ability to break down into natural amino acids that can be metabolized by the body, and minimal cytotoxicity, immune response, and inflammation [174,[188][189][190][191][192][193][194]. In addition, biopolymers can be easily functionalized to enhance their interactions with cells and provide an optimal platform for cellular activities and tissue functions.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…Multiple physical or chemical crosslinking sites can be genetically encoded so that the ELPs form networks, and reactive sites can be incorporated for controlled degradation. Specific ligands can also be added to impart functionality for cell adhesion and tissue growth [168,180,189,[195][196][197], and initial work by Urry et al demonstrated that ELPs cause minimal cytotoxicity and immune response when implanted [189,190].…”
Section: Genetically Engineered Polypeptidesmentioning
confidence: 99%
“…[24][25][26][27][28][29] ELPs are also promising scaffold materials for musculoskeletal and cardiovascular tissue engineering, as their peptide sequences are native to smooth and skeletal muscle, ligaments and other muscularskeletal tissues, and they show low cytotoxicity and no antigenic response in vivo. 11,19 In addition, ELPs may confer some benefits for cartilage tissue engineering application, as we have shown that the thermally-induced aggregated, "coacervate" phase of ELPs allows encapsulation of chondrocytes and human adipose derived stem cells while promoting a chondrogenic phenotype and cartilage matrix synthesis. 14,17 Although these studies have indicated the promise of ELPs for cartilage tissue engineering, these materials exhibited a narrow range of mechanical properties, which may limit their utility as scaffolds for cell-assisted regeneration, and provides the rationale for the development of crosslinking strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, implantation of synthetic elastomers or assembly of elastin peptides can replicate the mechanics of native elastin, but the absence of associated cell-signaling proteins (e.g., fibrillin) prevents the constructs from eliciting native responses from vascular smooth muscle cells (SMCs). [5][6][7][8] An alternative approach is to actively regenerate elastin structures in vivo and within tissueengineered constructs although the current unavailability of scaffolds that can provide cellular cues necessary to upregulate elastin synthesis and regenerate faithful mimics of native elastin limits this approach. 9,10 As mentioned above, elastic fibers are among the most difficult matrix structures to repair or regenerate because they contain other non-elastin protein components (e.g., fibrillin, elaunin) and have a highly regulated recruitment and deposition pattern and a multi-step hierarchical assembly process.…”
mentioning
confidence: 99%